Colonial Gothic to Māori renaissance essays in memory of Jonathan Mane-Wheoki - Stocker, Mark 1956-; McCarthy, Conal 1961- (Victoria University Press, 2017)
Jonathan Mane-Wheoki (1943-2014) was a much loved and respected academic and curator of broad and varied interests, who made an immense contribution to New Zealand art history over almost half a century. His scholarship was matched by a terrific generosity of spirit and personal charisma. Colonial Gothic to Māori Renaissance is a remarkable tribute to his memory from friends, colleagues and former students alike. Its contents are as varied and interesting as the man himself: Victorian church architecture and liturgy, mysticism, the New Zealand International Exhibition of 1906, the Toi Te Papa exhibition of 2006, traditional and contemporary Māori art, and the artists Thomas Benjamin Kennington, Gottfried Lindauer, Colin McCahon, Tony Fomison, Philip Clairmont and Emily Karaka are all included here. Beautifully illustrated and scholarly yet readable, this book is a powerful testament to the inspiration of a remarkable person
Keywords: Geschichte; Kunst; Maori; Neuseeland; Mane-Wheoki, Jonathan; Art historians / New Zealand; Art, New Zealand / History; Mahi toi; Waka toi; Festschriften; Pasifika; Festschrift